Persistent repair intermediates induce senescence - Femke M. Feringa; Jonne A. Raaijmakers; Michael A. Hadders; Chantal Vaarting; Libor Macůrek; Luuk Heitink; Lenno Krenning; René H. Medema (2018)
Abstract Double-stranded DNA breaks activate a DNA damage checkpoint in G2 phase to trigger a cell cycle arrest, which can be reversed to allow for recovery. However, damaged G2 cells can also permanently exit the cell cycle, going into senescence or apoptosis, raising the question how an individual cell decides whether to recover or withdraw from the cell cycle. Here we find that the decision to withdraw from the cell cycle in G2 is critically dependent on the progression of DNA repair. We show that delayed processing of double strand breaks through HR-mediated repair results in high levels of resected DNA and enhanced ATR-dependent signalling, allowing p21 to rise to levels at which it drives cell cycle exit. These data imply that cells have the capacity to discriminate breaks that can be repaired from breaks that are difficult to repair at a time when repair is still ongoing.